Developing leadership competencies for genomics integration through globally networked learning and education - Limoges, Jacqueline; Halkoaho, Arja; Laaksonen, Mari; Karwal, Muskaan (Frontiers in Medicine, 2024)
Aim: To describe the implementation and evaluation of an education strategy called the Globally Networked Learning – Genomics (GNL-G) used in Master’s courses in Canada and Finland. The study focused on the feasibility and effectiveness of GNL-G in developing leadership competencies for integrating genomics into practice. Methods: Interpretive description qualitative methodology was used to explore how GNL-G, global exchanges and assignments standardized with the Assessment of Strategies to Integrate Genomics in Nursing (ASIGN) tool influenced competency development. The Reporting Item Standards for Education and its Evaluation in Genomics (RISE2 Genomics) framework guided the design, implementation, evaluation, and reporting of GNL-G. Data included one-to-one interviews, written assignments, and reflections. Results: Interviews and assignment data from three cohorts of students for a total of ten Canadian and 11 Finnish master’s students participated in this study. The ASIGN Tool played a crucial role in facilitating students' analysis of their practice context and the development of leadership strategies. Participation in GNL-G enhanced students' confidence to lead efforts to integrate genomics, irrespective of their genomics expertise. Engagement with global peers emphasized the importance of incorporating equity, ethics, and social justice into leadership strategies for genomics integration. Conclusion: The GNL-G strategy enhanced leadership competencies for genomics integration in graduate students from Canada and Finland. The ASIGN Tool and global peer collaboration highlight the importance of innovative educational methods in preparing leaders for the complexities of genomics in healthcare.